Complement Component C4 Regulates the Development of Experimental Autoimmune Uveitis through a T Cell-Intrinsic Mechanism - Zhang, Lingjun; Bell, Brent A.; Li, Yan; Caspi, Rachel R.; Lin, Feng (Frontiers in Immunology, 2017)
In addition to its conventional roles in the innate immune system, complement has been found to directly regulate T cells in the adaptive immune system. Complement components, including C3, C5, and factor D, are important in regulating T cell responses. However, whether complement component C4 is involved in regulating T cell responses remains unclear. In this study, we used a T cell-dependent model of autoimmunity, experimental autoimmune uveitis (EAU) to address this issue. We compared disease severity in wild-type (WT) and C4 knockout (KO) mice using indirect ophthalmoscopy, scanning laser ophthalmoscopy, spectral-domain optical coherence tomography, and histopathological analysis. We also explored the underlying mechanism by examining T cell responses in ex vivo antigen-specific recall assays and in in vitro T cell priming assays using bone marrow-derived dendritic cells, splenic dendritic cells, and T cells from WT or C4 KO mice. We found that C4 KO mice develop less severe retinal inflammation than WT mice in EAU and show reduced autoreactive T cell responses and decreased retinal T cell infiltration. We also found that T cells, but not dendritic cells, from C4 KO mice have impaired function. These results demonstrate a previously unknown role of C4 in regulating T cell responses, which affects the development of T cell-mediated autoimmunity, as exemplified by EAU. Our data could shed light on the pathogenesis of autoimmune uveitis in humans.